Implant-Retained Nasal Prosthesis with Bar and Clip for a Patient with Total Rhinectomy: A Clinical Report - Fatima Balaghi; Mahya Hasanzade; Hamid Mahmood Hashemi; Simindokht Zarati (Tehran University of Medical Sciences, 2020)
The present clinical report describes the fabrication of an implant-retained prosthesis with bar and clip retention for a patient with total rhinectomy due to basal cell carcinoma (BCC). The nasal prosthesis was retained on the face by a reverse Y-shaped bar with horizontal and vertical extensions, resulting in favorable retention and function.